2017
DOI: 10.1016/j.tips.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the Paradigm: Protein Kinase C as a Tumor Suppressor

Abstract: The discovery in the 1980s that protein kinase C (PKC) is a receptor for the tumor-promoting phorbol esters fueled the dogma that PKC is an oncoprotein. Yet 30+ years of clinical trials for cancer using PKC inhibitors not only failed, but in some instances worsened patient outcome. The recent analysis of cancer-associated mutations, from diverse cancers and throughout the PKC family, revealed that PKC isozymes are generally inactivated in cancer, supporting a tumor suppressive function. In keeping with a bona … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 74 publications
2
90
0
Order By: Relevance
“…Consistent with the contrasting effects of individual PKC isozymes in promoting or suppressing tumor growth, it is now widely recognized that discrete members of this family can have either similar or opposite roles in a cellular context 46 . For example, early studies in fibroblasts showed inhibitory and promoting roles for PKCδ and PKCε, respectively, in cell growth and tumorigenesis 7 .…”
Section: Introductionmentioning
confidence: 95%
“…Consistent with the contrasting effects of individual PKC isozymes in promoting or suppressing tumor growth, it is now widely recognized that discrete members of this family can have either similar or opposite roles in a cellular context 46 . For example, early studies in fibroblasts showed inhibitory and promoting roles for PKCδ and PKCε, respectively, in cell growth and tumorigenesis 7 .…”
Section: Introductionmentioning
confidence: 95%
“…PKCα represent an actionable target. PKCα inhibitors have been unsuccessful in most cancers including glioblastomas, probably because loss of function was the prevalent mechanism in these cases 26 . In the case of ChGs, the inhibition of the neomorphic PKCα D463H could open a new perspective for specific targeting of this rare subtype of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…The PKC family of kinases includes the conventional PKC isoforms (α, β, and γ) with functional C1 and C2 domains, which bind diacylglycerol (DAG) and calcium, respectively, to promote membrane translocation and activation; the novel family members (δ, ε, η, and θ) with a functional C1 domain and with a nonfunctional C2 domain; and the atypical family members (ζ and ι), which lack functional C1 and C2 domains and are primarily regulated through protein–protein interactions. Because PKCs serve as the primary receptor for phorbol esters, which are tumor promoters that enhance carcinogenesis in skin cancer models , PKCs were initially classified as tumor promoters. Similar to diacylglycerol, phorbol esters bind the C1 domain of conventional and novel PKCs.…”
Section: Challenging the Tumor‐promoting Dogma Through Systematic Evamentioning
confidence: 99%